Systematic critical realist review of interventions designed to improve end‐of‐life care in care homes. (4th December 2019) - Spacey, Adam; Scammell, Janet; Board, Michele; Porter, Sam
Abstract: The demand for high‐quality end‐of‐life care is rising. Frequently evidenced concerns about the provision of end‐of‐life in care homes relate to inter‐disciplinary communication and engagement in advance care planning. A number of interventions employing different mechanisms have been designed to address these issues. Therefore, the aim of this systematic critical realist review was to describe and explain the effectiveness of interventions designed to improve end‐of‐life care in care homes. Electronic searches were conducted in ScienceDirect, MEDLINE, PubMed, PsychINFO, and CINAHL from January 2000 to August 2018. Forty one studies were included in the review. While most of the evidence identified in this review was not strong, there was evidence to suggest that education and inter‐professional collaboration can be effective intervention mechanisms for improving end‐of‐life care in care homes. High staff turnover was a significant contextual mechanism impacting on the sustainability of interventions. In terms of human agency, it is important to note a consistent finding related to the dedication and enthusiasm of care home staff who deliver end‐of‐life care.